2010
DOI: 10.1007/s12291-010-0047-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Changes in Glutathione-S-Transferase: Correlation with Total Plasma Antioxidant Potential and Red Cell Intracellular Glutathione

Abstract: The correlation between antioxidant capacity and oxidative damage during aging has been reported in several tissues in different species. Glutathione-S-transferases (GST) can metabolise endogenous and exogenous toxins and carcinogens by catalysing the conjugation of diverse electrophiles with reduced glutathione (GSH). We observe a significant (P < 0.001) increase in plasma GST activity as a function of human age (r = 0.5675). A significant (P < 0.001) positive correlation (r = 0.8979) is observed between GST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
3
12
0
2
Order By: Relevance
“…Increased level of GST seen in DTF persons with diabetes could be a manifestation of increased ROS generation as a result of prolonged hyperglycemia as well as a significant decreasing in GSH in mentioned group [48]. The correlation analysis revealed that GST and GSH are in a reverse correlation (r = -0.67, P < 0.01), which is in accord with previous studies [48,49]. Obviously, GST is highly likely to have a protective role in patients with diabetes after a tibia fracture but the increase in GST would not be sufficient enough to tackle ROS.…”
Section: Resultssupporting
confidence: 90%
“…Increased level of GST seen in DTF persons with diabetes could be a manifestation of increased ROS generation as a result of prolonged hyperglycemia as well as a significant decreasing in GSH in mentioned group [48]. The correlation analysis revealed that GST and GSH are in a reverse correlation (r = -0.67, P < 0.01), which is in accord with previous studies [48,49]. Obviously, GST is highly likely to have a protective role in patients with diabetes after a tibia fracture but the increase in GST would not be sufficient enough to tackle ROS.…”
Section: Resultssupporting
confidence: 90%
“…The correlation analysis revealed that GST and GSH are negatively correlated which is in sync with a previous study by Maurya and Rizvi 2010 [31]. As for the correlation of GST, OS markers and hyperglycemia, HbA1c is positively associated with increase in the activity of GST and MDA.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, elevation in liver and brain GST activities in male Wistar rats during aging have been reported by Kim et al [50] and Oztürk and Gümüşlü [51]. Also increase in plasma GST activity as a function of human age was described [52]. Elevation in GST activity/expression observed in this study could be explained as a compensatory mechanism against increased formation of oxidative stress products (e.g., organic hydroperoxides) accompanying process of aging.…”
Section: Discussionmentioning
confidence: 93%